Testing Practices and Incidence of Chlamydial and Gonococcal Infection in the Veterans Health Administration, 2009–2019. (25th September 2020) - Beste, Lauren A; Maier, Marissa M; Borgerding, Joleen; Lowy, Elliott; Hauser, Ronald G; Van Epps, Puja; Ohl, Michael; Ross, David; Chartier, Maggie
Abstract: Background: Chlamydia trachomatis and Neisseria gonorrhoeae cases reached a record high in the United States in 2018. Although active-duty military service members have high rates of chlamydia and gonorrhea infection, trends in chlamydia and gonorrhea in the Veterans Health Administration (VHA) system have not been previously described, including among patients living with human immunodeficiency virus (HIV) and young women. Methods: We identified all veterans in VHA care from 2009 through 2019. Tests and cases of chlamydia and gonorrhea were defined based on laboratory results in the electronic health record. Chlamydia and gonorrhea incidence rates were calculated each year by demographic group and HIV status. Results: In 2019, testing for chlamydia and gonorrhea occurred in 2.3% of patients, 22.6% of women aged 18–24 years, and 34.1% of persons living with HIV. The 2019 incidence of chlamydia and gonorrhea was 100.8 and 56.3 cases per 100 000 VHA users, an increase of 267% and 294%, respectively, since 2009. Veterans aged ≤34 years accounted for 9.5% of the VHA population but 66.9% of chlamydia and 42.9% of gonorrhea cases. Chlamydia and gonorrhea incidence rates in persons living with HIV were 1432 and 1687 per 100 000, respectively. Conclusions: The incidence of chlamydia and gonorrhea rose dramatically from 2009 to 2019. Among tested persons, those living with HIV had a 15.2-fold higher unadjusted incidence of chlamydia and 34.9-fold higher unadjusted incidence of gonorrhea compared with those not living with HIV. VHA-wide adherence to chlamydia and gonorrhea testing in high-risk groups merits improvement. Abstract : Incidence of chlamydia and gonorrhea in the Veterans Health Administration (VHA) was 100.8 and 56.3 cases per 100 000 in 2019, an increase of 267% and 294% since 2009. VHA rates of chlamydia and gonorrhea are lower than in the US population but rising steeply.